SINTESIS NANOPARTIKEL PERAK TERMODIFIKASI L-CYSTEINE SEBAGAI METODE ANALISIS: REVIEW JURNAL - Nisa, Hairin; Arif, Moh. Syaiful; Yusuf, Bohari (JURNAL ATOMIK, 2024)
Silver nanoparticles with a size of 1 to 100 nm with unique properties have many advantages that they are widely applied in the medical and industrial fields. Various methods can be carried out in synthesizing silver nanoparticles both physically, chemically and biologically. In the chemical method, it is done by reducing Ag+ ions into silver nanoparticles so that this method depends on reducing agents and stabilizers used. The use of different reducing agents greatly affects the size of the nanoparticles produced. Based on the literature review, sodium borohydride (NaBH4) has a strong ability to reduce Ag+ ions into silver nanoparticles become a small size. In addition, referring to previous studies if modified with L-cysteine, the silver nanoparticles formed can be stable for more than 2 months at room temperature storage. L-cysteine-modified silver nanoparticles from previous studies were used for colorimetric analysis of vitamin B1 detection in food and water samples, where the color change in silver nanoparticles from yellow to colorless showed remarkable chemical sensor selectivity for detecting target analytes.